Skimic FM: Optimization of Islamic Knowledge Through Radio Broadcasting in the School Environment - Fentika Zahra Qoirunnisa; Abdul Wahid; Rizka Ari Damayanti (Didaktika: Jurnal Kependidikan, 2024)
Currently, education in Indonesia applies an independent curriculum with one of the essential values, namely literacy. This is vital as a form of effort to improve language literacy skills and knowledge for students in the school environment. However, students' interest in reading is still relatively low due to changes in lifestyle in the digital era. To improve literacy and language skills, ICB Vocational School presents Skimic FM as an audio medium to deliver interesting, educational content. Through a qualitative approach, researchers find out how Skimic FM is an alternative way to optimize student knowledge from the results output literacy. As a result, the process of writing broadcast texts can optimize students' language literacy skills, then segment fun facts in Skimic FM broadcasting can provide an injection of knowledge for students to broaden their insight and perfect their knowledge gained from the literacy process. It is hoped that the results of this research can become a reference for other educational institutions in efforts to increase knowledge and language literacy skills.